Disrupting the Continuities Among Residential Schools, the Sixties Scoop, and Child Welfare: An Analysis of Colonial and Neocolonial Discourses - McKenzie, Holly A.; Varcoe, Colleen; Browne, Annette J; Day, Linda (International Indigenous Policy Journal, 2016)
In Canada, it is estimated that 3 times as many Indigenous children are currently in the care of the state compared to when the residential schools’ populations were at their peak. It is imperative that action be taken. This article explores the continuities among residential schools, the Sixties Scoop, and child welfare in Canada today. In particular, we examine how colonial and neocolonial discourses operate through and justify these policies and practices. We propose nine policy recommendations, which aim to transform child welfare and support Indigenous families to care for their children. Although transformative policy change is unlikely within this neocolonial and neoliberal climate, the recent change in federal leadership has made it more possible to move these policy recommendations forward.